Study on Organocatalytic Asymmetric Michael Addition in Aqueous Media by a Hydrogen-Bonding Catalyst and Application for Inhibitors of GABAB Receptor - Shim, Jae Ho; Hong, Yeonsun; Kim , Ji Hae; Kim, Hyeon Soo; Ha, Deok-Chan (Challenges and Advances in Chemical Science Vol. 7, 2021)
Catalysts based on (R, R)-1,2-diphenylethylenediamine are as chiral organic catalysts, applied to the asymmetric Michael addition to \(α\), \(β\)-unsaturated nitroalkenes under neutral conditions. The role of an aqueous medium for organic catalytic activity can be reversed concerning hydrophilic-hydrophobic function depending on the reaction conditions. In this study, to provide an environmentally friendly system, the thiourea-based catalyst substituted with 3,5-(CF3)2-Ph was used in water solvents. The hydrophobic effect of the substituent, provides fast reaction, high chemical yield, and mirror-image selectivity. This reaction allowed the preparation of GABAB agonists in an optically pure manner. Besides, GABA (\(γ\)-aminobutyric acid) analogs such as baclofen and phenibut were synthesized as R-type S-type with high optical purity. We demonstrated that R-baclofen induced a higher intracellular Ca2+ release than RS-baclofen. Taken together, our data show that as a drug, baclofen RS-type may induce differential calcium release activity depending on R and S-types. This will in turn induce differential GABAB receptor activation.